2013
DOI: 10.4012/dmj.2013-117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface treatment of glass-ionomers on surface free energy and bond strength of resin composite

Abstract: The purpose of this study was to determine the influence of surface treatment of glass-ionomer (GIC) on bond strength of resin composite and surface free energies. Specimens were prepared and divided into three groups as follows: without pretreatment (control), phosphoric acid etching, and air-abrasion. Adhesive was applied and resin composite was bonded. For conventional GIC, acid etching or air-abrasion increased bond strength (8.5-8.8 MPa) when compared with controls (4.7 MPa); however, RMGIC resulted in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The results of our study are in accordance with the results reported by Hashem et al [23]. Moreover, our study showed SBS values for surface-etched conventional GIC (Fuji IX, GC) bonded to RC similar to those obtained in previous studies [23,41,42]. The bond between GIC and RC is mediated by an adhesive system and relies on micromechanical retention [43,44], which can be enhanced by surface etching with phosphoric acid [41,42].…”
Section: Table 4 Failure Modes Presented By the Experimental Samples supporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are in accordance with the results reported by Hashem et al [23]. Moreover, our study showed SBS values for surface-etched conventional GIC (Fuji IX, GC) bonded to RC similar to those obtained in previous studies [23,41,42]. The bond between GIC and RC is mediated by an adhesive system and relies on micromechanical retention [43,44], which can be enhanced by surface etching with phosphoric acid [41,42].…”
Section: Table 4 Failure Modes Presented By the Experimental Samples supporting
confidence: 92%
“…Moreover, our study showed SBS values for surface-etched conventional GIC (Fuji IX, GC) bonded to RC similar to those obtained in previous studies [23,41,42]. The bond between GIC and RC is mediated by an adhesive system and relies on micromechanical retention [43,44], which can be enhanced by surface etching with phosphoric acid [41,42]. GIC develops most of its mechanical strength quickly (within 1 day to 1 week) [45], and this can explain the similar SBS values observed at different maturation time intervals.…”
Section: Table 4 Failure Modes Presented By the Experimental Samples supporting
confidence: 90%
“…As a result, we expected that there would also be differences in surface properties such as line roughness, surface roughness, gloss, discoloration, and wettability, but no correlations were found among them. Although the measurement results were not as similar as the other surface properties, and we are planning to investigate this in the future with consideration of surface free energy 25) .…”
Section: Surface Properties Of the New Resin Composite With Structuramentioning
confidence: 94%
“…Otsuka et al . [ 39 ] carried out a study to determine how acid etching and air abrasion of GIC and RMGIC affected the bond strengths while using a SEA. Increased bond strengths were observed for conventional GIC, but the opposite was observed for RMGICs.…”
Section: Resultsmentioning
confidence: 99%